Ours to share : coexisting in a crowded world - Jones, Kari (Kari Lynne), 1966- (Orca footprints., 2019)
Examines how overpopulation leads to unequal sharing of the Earth's social and natural resources. Discusses the human impact on the world, and ways people, communities, and countries are devising solutions to the crisis. Includes sidebars, fact boxes, color photographs, a glossary, and further resources.